Efektivitas Program Kurikulum Merdeka Belajar Di Sekolah Menengah Pertama Negeri 5 Sojol Kecamatan Sojol Kabupaten Donggala - Haikal; Tahili, Mashuri H.; Samsu, M Kafrawi Al-Kafiah (JPS: Journal of Publicness Studies, 2025)
The independent learning curriculum program at SMP Negeri 5 Sojol has been running well. However, constraints on human resource quality, competence, discipline, and insufficient supervision have prevented the program from being fully effective. This study aims to determine the effectiveness of the Independent Learning Curriculum program implementation at SMP Negeri 5 Sojol, Sojol District, Donggala Regency. Informants consisted of the principal, teachers, and seventh-grade students. The results of the study indicate that, in general, the implementation of the Independent Learning Curriculum at SMP Negeri 5 Sojol has been quite effective. Of the five indicators used, four aspects have been running well: apparatus quality, administrator competence, discipline, and supervision. Teachers are able to design and implement innovative, student-centered learning, and encourage student independence and creativity. School discipline is reflected in consistent teacher and student attendance and timely implementation of learning. Routine supervision by the principal and supervisors from the education office has contributed to improving the quality of learning. Meanwhile, the facilities and infrastructure aspect is still not running optimally. Limited technological facilities such as laptops and projectors, unstable internet connections, and inadequate laboratory equipment hinder learning that aligns with the principles of the Independent Curriculum.